Prospek Pengembangan Usahatani Tomat (Solanum Lycopersicum L.) di Kebun Fakultas Pertanian Universitas Nusa Nipa Maumere - Petrus Oktavianus Nurak; Yoseph Yakop Da Rato (Peneliti.net, 2022)
This study aims to determine the prospects for the development of tomato (Solanum lycopersicum) farming in the gardens of the Faculty of Agriculture, Nusa Nipa University. The results of the interviews were processed using purposive sampling method and SWOT analysis. The results showed that 1).there was an identification of internal and external factors consisting of strengths, weaknesses, opportunities and threats that supported the prospect of developing tomato farming. 2). The development of tomato farming is in quadrant I or an aggressive strategy, which uses strengths to take advantage of opportunities, namely: optimal utilization of production facilities and locations as places for production activities; optimizing land use with skilled labor in maintaining the quality of production for the prospect of organic tomatoes; strengthen the management of commercial farming in meeting the level of consumption of organic tomatoes.